Investigating flood prevention measures adopted in flood-prone areas of centurion, city of Tshwane metropolitan municipality - Kutumela, Ofentse Annah (University of the Witwatersrand, Johannesburg, 2024)
Globally, many countries such as Mozambique, Afghanistan, India, Brazil, the United States (US) and China among others continue to face the persistent challenge of climate change aftermaths, such as rising temperatures, extreme weather patterns and floods. South Africa is no exception, and similar to other countries, especially in the African continent, they lack strategy on how to respond to climate change impacts owing to continuously changing environmental patterns and trends. Therefore, the United Nations (UN) has drafted and implemented the Sendai Framework since 2015 to address disaster risk reduction worldwide, which goes concurrently with the Sustainable Development Goals (SDGs), in particular Goal 13 that deals with a call to Climate Action. The aim of this research was two-fold – first, to investigate prevention measures related to urban planning and land use management regulations that prevent flooding through disaster risk reduction. For instance, interrogating various policies, legislations, plans and programmes that have been sourced to prevent flooding in Centurion such as the Disaster Management Act, City of Tshwane (CoT) Disaster Risk Mitigation Plans, City of Tshwane Flood Incident Management Plan, Water Use Licence Policy, Flood Mitigation Plan and City Support Programme that are categorised as non-structural measures Secondly, to review flood risk reduction and the impact prevention measures that have been adopted in urban flood-prone areas in the CoT, particularly Centurion. The methodology used during this research was the qualitative approach. With this approach, I followed mixed methods research, where in the first stage, I collected primary data through one-on-one interviews through semi-structured interviews, while in the second stage, I conducted site visits as part of my observation. For sampling, I applied non-probability sampling technique known as purposive sampling to select research participants. In analysing the collected data, I adopted inductive thematic analysis to identify, interpret and report the existence of patterns in the data. The aim was to provide meaning to the findings and recommendations of the research. The findings reveal that protection of blue infrastructure is important as encroachment of wetlands continues to be a challenge. Nonetheless, this protection remains preventative measures in the lower catchment. Also, the integration of transboundary municipalities is important as it is not only the town planners' responsibility as professionals to implement disaster risk management but also all internal departments within a municipality. vi Failure to implement urban planning and land use management regulations, policies and or plans within the municipality, especially in Centurion, will potentially lead to significant implications, which may manifest themselves through an increase in debris, sinkholes, more deadly floods along the Hennops River, and adverse impacts as a result of changes in the environment.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: Flooding; Flood Prevention Measures; Flood-prone Areas; UCTD; SDG-13: Climate action